IMPLEMENTION OF OVERVIEW, KEY IDEAS, READ, RECORD, RECITE, REVIEW AND REFLECT ( OK5R) METHOD TO BOOST THE STUDENTS’ ABILITY IN READING COMPREHENSION METHOD (A Collaborative Classroom Action Research to the Second Year Student of SMP Negeri 1 Peusangan): IMPLEMENTION OF OVERVIEW, KEY IDEAS, READ, RECORD, RECITE, REVIEW AND REFLECT ( OK5R) METHOD TO BOOST THE STUDENTS’ ABILITY IN READING COMPREHENSION METHOD (A Collaborative Classroom Action Research to the Second Year Student of SMP Negeri 1 Peus - DAMAYANTI, IMA; LISTIA DEWI, SILVI (Journal of English Education and Social Science, 2021)
The problems of this research are: 1) How does overview, key ideas, read, record, recite, review and reflect ( OK5R ) Method increased students’ reading comprehension in descriptive text to the second-year students of SMP Negeri 1 Peusangan?. 2) How do the student respond toward overview, key ideas, read, record, recite, review and reflect ( OK5R ) Method in teaching learning process of reading comprehension to the second-year students of SMP Negeri 1 Peusangan?. The purposes of this research are: 1) To know the effectiveness of OK5R method to improve the students’ ability in reading comprehension in descriptive text to the second-year students of SMP Negeri 1 Peusangan. 2) To know the students’ response through OK5R method to the reading comprehension in descriptive text to the second-year students of SMP Negeri 1 Peusangan. The methodology of this research is collaborative action research; the setting of this research was SMP Negeri 1 Peusangan. The sample of this research was the second year Student of class VIII/6 which total Students were 28 students. The instruments were used in this research such as: test, observation sheet for the researcher and student, questionnaires, and field note.